Anti-TNF-α-induced lupus erythematosus in a patient with psoriasis – diagnostic controversy - Sobjanek, Michał; Wilkowska, Aleksandra; Sokołowska-Wojdyło, Małgorzata; Michajłowski, Igor; Roszkiewicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Drug-induced lupus erythematosus (DILE) is defined as lupus-like syndrome related to drug exposure. DILE is associated with more than 80 different medications. Anti-TNF-α-induced lupus is reported in less than 0.5% of all treated patients. About 130 cases of DILE connected with anti-TNF-α therapy have been described. Most of them are associated with infliximab or etanercept; only a few cases are adalimumab induced. Objective . To present diagnostic and therapeutic problems with a patient with psoriasis treated with anti-TNF-α drugs in whom symptoms similar to DILE were observed. Case report . A 47-year-old woman with a 20-year history of psoriasis and 15-year history of psoriatic arthritis was treated with infliximab, etanercept and adalimumab. During the treatment with adalimumab exacerbation of cutaneous lesions and joint symptoms was noted. Antinuclear antibodies (ANA) and lupus band test were strongly positive. Adalimumab therapy was discontinued and treatment with ustekinumab was introduced. The cutaneous and joint symptoms progressively faded. Conclusions . During anti-TNF-α therapy an elevated titre of ANA is frequently observed. However, anti-TNF-α induced DILE is observed rarely and the disease has a benign course. We present diagnostic problems in a patient with psoriasis treated with anti-TNF-α drugs in whom symptoms similar to DILE were observed.